Questão social e as inflexões no exercício profissional do assistente social nas promotorias de justiça - Gomes, Gláubia Oliveira (2013)
The present Master's Dissertation entitled Social Issues and the inflections in the professional practice of the social worker in the Promoters of Justice, which aims to analyze the repercussions of the social issues about the professional practice of the Social workers in the Prosecutors of Justice correlating these to the ethical-political project of the profession.In specific terms, it aims to comment the process of constitution of the social issues in Brazil and the consequent opening of the field socio-juridical for the profession of Social work as from the 1988 Constitution; discuss about the tools and techniques used by professionals in the work routine, and ravel their political dimension in the context of the Prosecutors of Justice. Methodologically, it is a theoretical bibliographic and documentary research. It’s based in the theoretical and methodological perspective of revisit the available literature about the theme from the study about the socio-juridical field in the reports and articles published in the I, II and III National Meeting of Social Work in the Public Ministry. The study also evidence other documents and articles published about the theme. To the reach of the objectives proposed, the theoretical research was based in the study of categories, such as: social issues, socio-juridical field, judicialization of the social issue and professional practice of the social worker.The access to the literature studied provided a greater knowledge about the theme, although it is recognized that the production of the knowledge in socio-juridical field is still scarce, and it constitutes labor market in expansion for the Social worker.The analytical considerations elaborated around the repercussions of the "social issue" about the professional practice of the Social worker in the Public Ministry requested a historical study of insertion of the profession in the socio-juridical and socio-occupational area in specific. It also required analyzing the current situation, which indicates that the societal transformations have not served to increase the opportunities for fruition and distribution of product of the collective work, thus, aggravating the expressions of the social issues. Based in studies, attested the growing institutional demand, especially in organisms of Justice by the intervention of the professional social worker, based on individualization of attendance. The materiality of the main demands within this institutional universe, attributed to the social worker occurs in attendance the victims of violence and in the inspection of social welfare entities, evidencing the character controller of the institution. In addition, this study suggests that the insertion of Social worker in this context presents the possibility that from the professional intervention in critical perspective it is possible to bring the contradictions inherent in the current production process. In conclusive terms, it is verified that the reflection of the contributions derived from the bibliographic study that indicates to increasing insertion of the judicialization of social issue in the panorama socio juridical and facing this reality, challenges are put to the critical professional practice.